Electrodeposition of Magnetic SmCo Films from Deep Eutectic Solvents and Choline Chloride-Ethylene Glycol Mixtures. Issue 13 (1st January 2017) - Panzeri, Gabriele; Tresoldi, Matteo; Rinaldi, Christian; Magagnin, Luca
Abstract : Suitability of mixtures based on ethylene glycol and choline chloride is evaluated for the electrodeposition of magnetic SmCo alloys. Deep eutectic solvents (DES) are characterized by a wide electrochemical window, allowing the electrodeposition of metallic elements having a highly negative reduction potential. Electrodeposition of unconventional metals with reduction potential well below hydrogen evolution one is, in principle, feasible (e.g. Sm). Moreover, the limited presence of water during the growth of SmCo alloys may reduce oxidation and consequently improve the magnetic properties with respect to the employment of an aqueous bath. Deposits composition is strongly affected by process parameters and bath composition. Increasing choline chloride concentration and/or adding glycine to the solution allows to achieve higher Sm content in the deposit. Potentiostatic electrodeposition has been carried out in a conventional three electrodes cell, with potential interval selected from −0.7 V vs Ag wire to −0.95 V vs Ag wire, keeping the bath under stirring at 70°C. Magnetic SmCo films with composition from 0 to 50 wt% Sm have been obtained with coercivity up to 270 Oe.